Contribution of ankle-foot orthosis moment in regulating ankle and knee motions during gait in individuals post-stroke. (June 2017) - Kobayashi, Toshiki; Orendurff, Michael S.; Singer, Madeline L.; Gao, Fan; Foreman, K. Bo
Abstract: Background: Ankle-foot orthosis moment resisting plantarflexion has systematic effects on ankle and knee joint motion in individuals post-stroke. However, it is not known how much ankle-foot orthosis moment is generated to regulate their motion. The aim of this study was to quantify the contribution of an articulated ankle-foot orthosis moment to regulate ankle and knee joint motion during gait in individuals post-stroke. Methods: Gait data were collected from 10 individuals post-stroke using a Bertec split-belt instrumented treadmill and a Vicon 3-dimensional motion analysis system. Each participant wore an articulated ankle-foot orthosis whose moment resisting plantarflexion was adjustable at four levels. Ankle-foot orthosis moment while walking was calculated under the four levels based on angle-moment relationship of the ankle-foot orthosis around the ankle joint measured by bench testing. The ankle-foot orthosis moment and the joint angular position (ankle and knee) relationship in a gait cycle was plotted to quantify the ankle-foot orthosis moment needed to regulate the joint motion. Findings: Ankle and knee joint motion were regulated according to the amount of ankle-foot orthosis moment during gait. The ankle-foot orthosis maintained the ankle angular position in dorsiflexion and knee angular position in flexion throughout a gait cycle when it generated moment from − 0.029 (0.011) to − 0.062 (0.019) Nm/kg (moment resisting plantarflexion was defined as negative). Interpretations: Quantifying the contribution of ankle-foot orthosis moment needed to regulate lower limb joints within a specific range of motion could provide valuable criteria to design an ankle-foot orthosis for individuals post-stroke. Highlights: An ankle-foot orthosis affects ankle and knee motion during gait in individuals post-stroke. Bench testing and gait analysis were performed to measure ankle-foot orthosis's moment. The amount of the orthotic moment necessary to regulate the ankle and knee motion was quantified. These data are valuable in designing an ankle-foot orthosis for individuals post-stroke.